GREEN SYNTHESIS OF COPPER OXIDE NANOPARTICLE FROM PLANT EXTRACT AND ITS ANTIBACTERIAL ACTIVITY - Saloki, Arushi; Daharwal, Sanjay J (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present study focused on the synthesis of copper oxide nanoparticles (CuO NPs) using cinchona bark extract, its characterization, and studies on antibacterial activities. Methods: The CuO NPs were synthesized using 1 mM CuSO4.5H2O with 2% (m/v) aqueous bark extract of cinchona under optimum conditions (pH = 11). Result: The formation of CuO NPs has been confirmed first by the color change from colorless to light yellow and then to Brownish. Using a UV-Visible spectrophotometer the kinetics of the reaction was studied that showed surface plasmon resonance at 382nm. Zeta potential and particle size were calculated to be -15.2mV and, 197 nm respectively. The antibacterial activity of CuO NPs was tested against gram-positive and gram-negative culture, which shows desirable activity. Conclusion: The outcome of the study demonstrates that cinchona bark extract serves as a reducing and stabilizing agent, transforming Cu2+ metallic ions into CuO nanoparticles The green synthesis of the copper oxide nanoparticles (CuO NPs) using cinchona bark extract, characterization, and their antibacterial activity was successfully carried out and gram-positive (S. aureus) shows more activity compared to gram-negative (E.coli) bacteria.